Simulation Numérique Du Système Bielle Manivelle Du Moteur à Combustion Interne - ثابت, دريهم; عبد الكريم, بن علي; عبد الرزاق, بوراس (University of El-Oued, 2021)
"Abstract The main function of the piston of an IC engine is to receive the pulse of the expanding gas and transmit the energy to the crankshaft through the connecting rod this is called the crank connecting rod system, the current goal of this project is to assemble the piston, connecting rod and crankshaft for 4-stroke gasoline engine, the parts are designed and assembled using SolidWorks 3D modeling software, where was the material chosen for the three parts ( Aluminum alloy) for piston and connecting rod, and (steel) for crankshaft, the mesh and finite element analysis is done in ANSYS program and two types of simulations are done in this program (modal analysis and static analysis), l modal analysis is used to determine the vibration characteristics (natural frequencies and mode shapes) of the three components as it was the maximum value of the natural frequency high at mode 6, Structural analysis is used to determine the shifts elements and stresses and deformation, safety factor under statics." "ملخص تتمثل الوظيفة الرئيسية لمكبس محرك الاحتراق الداخلي في استقبال نبضة الغاز المتوسع ونقل الطاقة إلى العمود المرفقي من خلال قضيب التوصيل وهذا ما يسمى نظام قضيب توصيل الكرنك ، والهدف الحالي لهذا المشروع هو تجميع المكبس ، قضيب التوصيل والعمود المرفقي لمحرك البنزين رباعي الأشواط ، تم تصميم الأجزاء وتجميعها باستخدام برنامج النمذجة SolidWorks ثلاثية الأبعاد ، حيث تم اختيار المادة للأجزاء الثلاثة (سبائك الألومنيوم) للمكبس وقضيب التوصيل ، و (الصلب) للعمود المرفقي ، يتم إجراء تحليل الشبكة والعناصر المحدودة في برنامج ANSYS ويتم إجراء نوعين من المحاكاة في هذا البرنامج (التحليل النموذجي والتحليل الساكن) ، ويستخدم التحليل النموذجي لتحديد خصائص الاهتزاز (الترددات الطبيعية وأشكال الوضع) للمكونات الثلاثة حيث كانت القيمة القصوى للتردد الطبيعي عالية في الوضع 6 ، يتم استخدام التحليل الإنشائي لتحديد التحولات العناصر والضغوط والتشوه ، عامل الأمان تحت السكون"
Energétique مذكرة ماستر تخصص
Keywords: "Key words: IC engine, crank connecting rod system, finite elements, transmit energy, gasoline engine, 4 strokes. "; "الكلمات المفتاحية: محرك الاحتراق الداخلي، نظام قضيب توصيل كرنك، عناصر محدودة، ينقل الطاقة، محرك بنزين، 4 أشواط."